High‐sensitivity CRP is elevated in pregnant women with overweight and obesity and modulated by gestational weight gain - Ann‐Christin Tallarek; Tanja Zeller; Alina Goßling; Caroline Kellner; Gudula Hansen; Mirja Pagenkemper; Charlotte Humke; Evelyn Annegret Huhn; Christopher Urbschat; Petra Clara Arck; Anke Diemert (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The global obesity epidemic presents a growing challenge in perinatal medicine and obstetrics, as it is associated with a higher risk of adverse maternal and perinatal outcomes. In addition to metabolic disturbances, obesity contributes to chronic low‐grade inflammation. This study aims to investigate the relationship between maternal overweight, obesity, and excessive weight gain during pregnancy and high‐sensitivity C‐reactive protein (hs‐CRP), an acute‐phase reactant of inflammation and infection in maternal serum. Material and Methods The PRINCE (Prenatal Identification of Children's Health) study is a prospective longitudinal pregnancy cohort conducted at the University Medical Centre Hamburg‐Eppendorf in Germany. In this study, biosamples and metadata were collected from 2011 to 2023. Hs‐CRP levels were measured in each trimester among 582 healthy, low‐risk women. Participants were categorized into weight classes based on their body mass index. Weight gain during pregnancy was evaluated according to the recommendations of the Institute of Medicine. For statistical analysis, the Wilcoxon and Kruskal–Wallis tests were employed for continuous variables, whereas the Mann–Whitney test was used for binary groups. Results Hs‐CRP levels are significantly higher in overweight and obese pregnant women throughout their pregnancy. During the first trimester, hs‐CRP compared to those of normal‐weight individuals (mean 3.4 mg/L; 95% CI 3.1 to 3.7) showed a 1.7‐fold increase in overweight (mean 5.9 mg/L; 95% CI 5.0 to 6.7; p < 0.0001) and a 2.7‐fold increase in obesity (mean 9.3 mg/L; 95% CI 7.6 to 11.0; p < 0.0001). Excessive weight gain during pregnancy is more common among overweight women (67%) and is associated with 1.5‐fold heightened hs‐CRP levels in the third trimester (mean 5.6 mg/L; 95% CI 4.7 to 6.4), compared to overweight women who follow the recommended weight gain guidelines (mean 3.7 mg/L; 95% CI 2.9 to 4.4; p = 0.009). Conclusions Overweight and obesity, along with excessive gestational weight gain in individuals with preexisting overweight status, correlate with elevated levels of hs‐CRP during pregnancy. This phenomenon indicates chronic low‐grade inflammation in adipose tissue.